BCG Vaccination and Spinal Tuberculosis in Non-Malnourished and/or Non-HIV Infected Children at Dr. Soetomo General Academic Hospital, Surabaya - Albarok, Muhammad Abdir Rahman; Faris, Muhammad; Endaryanto, Anang; Setyoningrum, Retno Asih (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: The Bacillus Calmette-Guérin (BCG) vaccination has been widely implemented in Indonesia, but cases of spinal tuberculosis (TB) in children can still be found. There are significant and moderate relationships between BCG vaccination and the occurrence of spinal TB in children.   Abstract Introduction: Spinal tuberculosis (TB) is an extrapulmonary form of TB that affects the spine. The Bacillus Calmette-Guérin (BCG) vaccination program, which has been implemented to prevent TB, should have prevented this type of TB. However, cases of this disease in children can still be found. This study aimed to determine whether there was a relationship between BCG vaccination and the occurrence of spinal TB in children. Methods: This case-control analytic observational study was performed based on medical record data. The study subjects of each group, both case and control, were taken from pediatric TB patients at Dr. Soetomo General Academic Hospital, Surabaya, from 2017 to 2021. Patients with malnutrition and/or human immunodeficiency virus (HIV) infection were excluded. Statistical analyses were performed using Fisher’s exact test. Results: There were 9 patients in total within each group. Most were 12-17 years old, and the ratio of male by female was 1.25:1. There were 4 out of 9 (44%) spinal TB patients and 9 of 9 (100%) patients with no spinal TB who all received BCG vaccination. The statistical test indicated a significant (p=0.029) and moderate (C=0.527) relationship between BCG vaccination and the occurrence of spinal TB in children. Conclusion: The Bacillus Calmette-Guérin vaccination should be able to prevent the new occurrence of spinal TB in children.